Ultrasonic-assisted extraction of sunflower seeds oil: kinetic and thermodynamics study: article - Alias, Nurul Aqilah; Mohd Fuad, Faiznur (2019)
This study has been conducted to evaluate the kinetic and thermodynamics of oil extraction from sunflower seeds using ultrasonic-assisted extraction (UAE). The first scope was one factor at a time (OFAT). The OFAT study involved different type of solvent, extraction time, temperature, and L/S ratio. The maximum oil yield (54.4%) was obtained with the used of ethyl acetate as solvent at 20 minutes, 40oC, and 100 ml/g of L/S ratio. Second order kinetic model was used in describing the extraction process. The model coefficients were observed with determination coefficient (R2 ≥ 0.9779) and MRPD value 2.0692% – 9.5936%. Thermodynamics study showed that the activation energy in this extraction process was 1526.78 J mol-₁